Evaluation of platelet function in thrombocytopenia. (3rd April 2018) - Skipper, Mette Tiedemann; Rubak, Peter; Stentoft, Jesper; Hvas, Anne-Mette; Larsen, Ole Halfdan
Abstract: Whole blood aggregometry is a functional assay for determination of platelet function. Until now, whole blood aggregometry has not been considered feasible at low platelet counts. Hence, the objectives of the present study were to explore platelet function in thrombocytopenia using a novel index of impedance aggregometry adjusted for platelet count and evaluate the association to platelet function assessed by flow cytometry. Hirudin anticoagulated blood was collected from 20 healthy volunteers, 20 patients with primary immune thrombocytopenia (ITP), and 17 hematological cancer patients. Platelet function was analyzed by impedance aggregometry and by flow cytometry. Collagen, adenosine diphosphate, thrombin receptor agonist peptide-6, and ristocetin were used as agonists for both analyses. Thrombocytopenia in healthy whole blood was induced in vitro employing a recently published method. Platelet aggregation of thrombocytopenic patients was evaluated relative to the aggregation of healthy volunteers at the same platelet count. In flow cytometry, platelet function was described as expression of the platelet surface glycoproteins: bound fibrinogen, CD63, and P-selectin. Similar platelet counts were obtained in the patient groups ( p = 0.69) (range: 13–129 × 10 9 /l). Aggregation adjusted for platelet count was significantly increased in ITP patients compared to healthy platelets across all agonists. The platelet aggregation was high in the 95% prediction interval, with 18 ITP patients above the prediction interval in at least two agonists. In contrast, the platelet aggregation was low in the prediction interval in cancer patients, and three cancer patients with platelet aggregation below the prediction interval in at least one agonist. ITP patients displayed increased expression of bound fibrinogen and CD63 following activation, compared with particularly cancer patients, but also compared with healthy platelets. This study demonstrated the feasibility of a novel approach to perform platelet function analyses in thrombocytopenia using impedance aggregometry adjusted for platelet count.